Acid and alkali corrosion resistant plastic and preparation method thereof

Through the coupling reaction of 2-hydroxysuccinic acid with nanosilicon oxide or nanoalumina, the compatibility of nanoparticles is improved, and the problem of poor strength of existing acid-base corrosion-resistant polypropylene materials is solved, and higher acid-base corrosion resistance and mechanical properties are achieved.

CN116622162BActive Publication Date: 2025-03-28SICHUAN CHANGYAN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310825252.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-03-28
Estimated Expiration
2043-07-06

AI Technical Summary

Technical Problem

During the blending and modification process of existing acid and alkali corrosion resistant polypropylene materials, due to the compatibility problems between components, the strength of composite materials is poor and cannot be applied to more fields.

Method used

Through the coupling reaction of 2-hydroxysuccinic acid with nanosilicon oxide or nanoalumina, the surface properties of the nanoparticles are improved, their dispersion and compatibility in the polymer are improved, and the compatibility between the nanoparticles and the polypropylene matrix is ​​increased, thereby improving the strength and stability of the polypropylene material.

Benefits of technology

It effectively improves the acid and alkali corrosion resistance and mechanical properties of polypropylene materials, and enhances the stability and application performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004324966680000021
    Figure BDA0004324966680000021
  • Figure BDA0004324966680000031
    Figure BDA0004324966680000031
  • Figure BDA0004324966680000041
    Figure BDA0004324966680000041
Patent Text Reader

Abstract

The invention discloses an acid-base corrosion resistant polypropylene material, which has the characteristics of high strength and good corrosion resistance. The components include polypropylene, modified nanoparticles, a nucleating agent and an antioxidant; wherein the modified nanoparticles are the product of coupling 2-hydroxysuccinic acid with nano-silicon oxide or nano-aluminum oxide. The product enhances the compatibility of nanoparticles and polymers through the coupling reaction of 2-hydroxysuccinic acid with nano-silicon oxide or nano-aluminum oxide, so that the components can form a system with strong interaction with each other, thereby improving the mechanical properties and acid-base corrosion resistance of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polypropylene-based acid and alkali corrosion-resistant plastic and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a thermoplastic resin belonging to the polyolefin plastics, which has the characteristics of light weight, high strength, heat resistance and transparency. Polypropylene can be made into products of various shapes through extrusion, injection molding, blow molding and other processing technologies, and is widely used in packaging, medical, automotive, electrical appliances and other fields. However, polypropylene is susceptible to ultraviolet rays and oxides, easy to age, and easy to crack under long-term erosion of acid and alkali liquids or other liquids, thus affecting normal functional use. Therefore, in order to overcome the shortcomings of polypropylene, an appropriate amount of acid and alkali corrosion-resistant substances are often added through copolymerization, blending, filling and other modification methods, so that the material itself or the main structure is not dissolved or destroyed by the corrosive medium, and the components play a synergistic role to improve the overall performance of the modified material. At present, the acid and alkali corrosion-resistant polypropylene modification technology can be achieved by physical methods, chemical methods and changing the crystal form of the polymer. However, in the blending modification of these systems, due to the compatibility problems between various components, the components are separated during the blending process, which often makes the strength of the composite material poor and cannot be applied to more fields.

[0003] Chinese patent CN102838866A discloses a polyurethane and polypropylene nano-modified material, the formula of which is polyurethane polypropylene plasticizer, polyolefin and polyvinyl chloride functional modifier, nano material, stabilizer and additive. However, the nano material cannot be evenly dispersed in the polypropylene matrix, and the strength of the composite material is poor.

[0004] Chinese patent CN103073798B discloses a polypropylene composition for a water heater plastic liner and a preparation method thereof, wherein the composition comprises copolymerized polypropylene, talcum powder / calcium carbonate filler, antioxidant, stabilizer and additive. However, since talcum powder / calcium carbonate particles will generate stress with polypropylene, there will be weak points in the internal structure of the product, and the strength of the composite material is poor.

[0005] Therefore, there is an urgent need to develop a plastic that is resistant to acid and alkali corrosion and has better compatibility between components. Summary of the invention

[0006] Based on the defects in the prior art, the purpose of the present invention is to provide an acid-base corrosion resistant polypropylene material, which has the advantages of light weight, good mechanical properties, good acid-base corrosion resistance, etc. The main components of the acid-base corrosion resistant polypropylene material include polypropylene, modified nanoparticles, a nucleating agent and an antioxidant. Among them, the modified nanoparticles are the product of 2-hydroxysuccinic acid coupled with nano silicon oxide or nano aluminum oxide.

[0007] The present invention uses a coupling reaction between 2-hydroxysuccinic acid and nano silicon oxide or nano aluminum oxide, and the 2-hydroxysuccinic acid can undergo an esterification reaction with the hydroxyl groups on the surface of the nanoparticles to form a stable ester bond, thereby changing the properties of the surface of the nanoparticles, improving the dispersibility and stability of the nanoparticles in the polymer, and increasing the compatibility between the nanoparticles and the polypropylene matrix;

[0008] The hydroxyl groups on the surface of nano-silicon oxide or nano-aluminum oxide and the hydroxyl groups in the 2-hydroxysuccinic acid molecules can form hydrogen bonds, thereby increasing the interaction between molecules, promoting the formation of a tighter structure between the two, and further improving the performance and stability of the composite material.

[0009] Therefore, the properties of nanoparticles can be effectively improved and the application performance of polypropylene materials can be enhanced through the coupling reaction of 2-hydroxysuccinic acid and nano-silicon oxide or nano-aluminum oxide.

[0010] The acid and alkali corrosion resistant polypropylene material comprises polypropylene, modified nano particles, a nucleating agent and an antioxidant.

[0011] Wherein, the modified nanoparticles are the product of coupling 2-hydroxysuccinic acid with nano silicon oxide or nano aluminum oxide.

[0012] Further, the molecular weight of the polypropylene is 8-15w;

[0013] Further, the nucleating agent is selected from di(p-methylbenzylidene)sorbitol;

[0014] Further, the antioxidant is selected from antioxidant 1076, antioxidant 1024 or antioxidant 1010;

[0015] Furthermore, the acid and alkali corrosion resistant plastic includes the following components in parts by mass:

[0016]

[0017] Another object of the present invention is to provide a method for preparing the above-mentioned acid and alkali corrosion resistant polypropylene plastic, which comprises the following steps:

[0018] S1. Preparation of modified nanoparticles: 2-hydroxysuccinic acid is dissolved in water, and then nano-silicon oxide and nano-aluminum oxide are added, heated to 90°C-100°C and subjected to ultrasonic reaction, and then centrifuged and washed, and dried at room temperature to obtain the modified nanoparticles;

[0019] S2. blending the modified nanoparticles, polypropylene, a nucleating agent, an antioxidant and other ingredients;

[0020] S3. The blended materials are fed into an extruder for melt blending at a melting temperature of 180°C-200°C, and extruded to obtain the acid- and alkali-resistant plastic.

[0021] Further, the molar ratio of 2-hydroxysuccinic acid, nano silicon oxide and nano aluminum oxide in S1 is 1:0.3:0.3-1:0.5:0.5;

[0022] Further, the heating temperature in S1 is 90°C-100°C;

[0023] Furthermore, the melting temperature in S3 is 180°C-200°C.

[0024] The present invention has the following beneficial effects:

[0025] 1. Through the above preparation method, the acid and alkali corrosion resistance of polypropylene materials can be improved, and the material itself or the main structure can be protected from being dissolved or destroyed by the corrosive medium.

[0026] 2. Through the coupling reaction of 2-hydroxysuccinic acid and nano-silicon oxide or nano-aluminum oxide, the surface properties of nanoparticles are effectively improved, their dispersibility and compatibility in polymers are improved, the compatibility between nanoparticles and polypropylene matrix is ​​increased, and the strength and stability of polypropylene materials are enhanced. DETAILED DESCRIPTION

[0027] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0028] The polypropylene described in the embodiment of the present invention is purchased from Shanghai Shunshi Plastic Chemical Co., Ltd., model PPH-T03;

[0029] The 2-hydroxysuccinic acid described in the embodiments of the present invention was purchased from Guangzhou Desheng Chemical Co., Ltd.

[0030] The nano-silicon oxide and nano-aluminum oxide described in the embodiments of the present invention, the nano-silicon oxide model is VK-SP30S, and the nano-aluminum oxide model is VK-L06, which are purchased from Hangzhou Wanjing New Materials Co., Ltd.;

[0031] The di(p-methylbenzylidene) sorbitol used as the nucleating agent in the embodiments of the present invention was purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.;

[0032] The antioxidant 1010 in the embodiment of the present invention was purchased from Nanjing Milan Chemical Co., Ltd.;

[0033] The parts in the embodiments of the present invention are all parts by mass.

[0034] Example 1

[0035] A plastic resistant to acid and alkali corrosion, comprising the following components in parts by mass:

[0036]

[0037] The preparation of the modified nanoparticles is as follows:

[0038] S1. Add 10 mmol of 2-hydroxysuccinic acid into water, stir at 50°C until completely dissolved, then add 0.3 mmol of nano silicon oxide and 0.3 mmol of nano aluminum oxide into the solution, continue stirring until uniformly dispersed, and obtain an intermediate product;

[0039] S2, heating the intermediate product to 95°C, and simultaneously performing ultrasonic treatment at an ultrasonic power of 350W for 40 minutes. After the reaction is complete, stop heating and ultrasonic reaction, and wait for the reaction liquid to cool to room temperature;

[0040] S3, centrifugally separating the reaction liquid, pouring out the supernatant liquid, leaving the precipitate. Washing the precipitate with deionized water, repeating 3 times. Placing the washed precipitate in a dryer, drying at room temperature until completely dry, to obtain the modified nanoparticles.

[0041] The preparation of the above-mentioned acid and alkali corrosion resistant plastic is as follows:

[0042] S1. Weigh 100 parts of polypropylene, 10 parts of modified nanoparticles, 0.3 parts of nucleating agent and 2 parts of antioxidant 1010, put them into a high-speed mixer, and mix them thoroughly until a uniform mixture is obtained;

[0043] S2, putting the mixture into a twin-screw extruder, setting the melting temperature of the extruder to 180° C. and the melting time to 20 minutes, extruding the molten material to obtain the acid- and alkali-resistant plastic.

[0044] Example 2

[0045] A plastic resistant to acid and alkali corrosion, comprising the following components in parts by mass:

[0046]

[0047] The preparation of the modified nanoparticles is as follows:

[0048] S1. Add 10 mmol of 2-hydroxysuccinic acid into water, stir at 50°C until completely dissolved, then add 0.3 mmol of nano silicon oxide and 0.3 mmol of nano aluminum oxide into the solution, continue stirring until uniformly dispersed, and obtain an intermediate product;

[0049] S2, heating the intermediate product to 95°C, and simultaneously performing ultrasonic treatment at an ultrasonic power of 350W for 40 minutes. After the reaction is complete, stop heating and ultrasonic reaction, and wait for the reaction liquid to cool to room temperature;

[0050] S3, centrifugally separating the reaction liquid, pouring out the supernatant liquid, leaving the precipitate. Washing the precipitate with deionized water, repeating 3 times. Placing the washed precipitate in a dryer, drying at room temperature until completely dry, to obtain the modified nanoparticles.

[0051] The preparation of the above-mentioned acid and alkali corrosion resistant plastic is as follows:

[0052] S1. Weigh 100 parts of polypropylene, 15 parts of modified nanoparticles, 0.3 parts of nucleating agent and 2 parts of antioxidant 1010, put them into a high-speed mixer, and mix them thoroughly until a uniform mixture is obtained;

[0053] S2, putting the mixture into a twin-screw extruder, setting the melting temperature of the extruder to 180° C. and the melting time to 20 minutes, extruding the molten material to obtain the acid- and alkali-resistant plastic.

[0054] Comparative Example 1

[0055] The preparation method, ingredients used and mass fractions of the plastic in Comparative Example 1 are the same as those in Example 1. The only difference is that the plastic in Comparative Example 1 does not contain modified nano-silicon oxide and modified nano-aluminum oxide, but is replaced by conventional nano-silicon oxide and nano-aluminum oxide in equal mass fractions.

[0056] Test Example 1

[0057] After drying the acid-base corrosion-resistant plastic pellets obtained in the above Example 1 and Comparative Examples 1-2, the injection-molded test strips were prepared to test the mechanical properties, and 5 samples were taken for each test of the mechanical properties. The test method was carried out in accordance with the ASTM D638-02 plastic tensile properties test standard.

[0058] Specifically, the samples prepared as above were placed in an outdoor open-air environment for 60 days (with an average daily temperature of 24°C, 17 sunny days, 29 cloudy or overcast days, and 14 rainy days), and then the mechanical properties were tested and the data were recorded to see whether the mechanical properties of the samples in the same group were significantly different.

[0059] The results are shown in Table 1.

[0060] Table 1 Mechanical properties test of the corrosion-resistant acid-base plastics obtained in the embodiments and comparative examples

[0061]

[0062] It can be seen from Table 1 that different samples in different groups have large differences in tensile strength after long-term exposure to outdoor open-air environment. Compared with Comparative Example 1, the average tensile strength of the sample in Example 1 is slightly lower, indicating that its overall aging degree is slightly lighter;

[0063] The tensile strength values ​​of the samples in Example 1 are relatively stable, and the maximum difference in tensile strength is 0.8 MPa, which indicates that the dispersion of the modified nanoparticles in Example 1 is relatively uniform, and the structure formed by the modified nanoparticles and the polypropylene matrix is ​​tighter and more stable. However, the tensile properties of the samples in Comparative Example 1 show a large difference, and the maximum difference in tensile strength is 1.8 MPa, which indicates that the nanoparticles in Comparative Example 1 are unevenly distributed in the material.

[0064] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0065] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A plastic resistant to acid and alkali corrosion, characterized in that: The acid and alkali corrosion resistant plastic comprises the following components in parts by weight: 100-120 parts of polypropylene, 10-20 parts of modified nanoparticles, 0.2-0.5 parts of nucleating agent, and 1-3 parts of antioxidant; in, The modified nanoparticles are products of coupling 2-hydroxysuccinic acid with nano silicon oxide and nano aluminum oxide; The molar ratio of 2-hydroxysuccinic acid, nano silicon oxide and nano aluminum oxide is 10:0.3:0.3; The preparation method of the acid- and alkali-resistant plastic comprises the following steps: S1. Preparation of modified nanoparticles: dissolving 2-hydroxysuccinic acid in water, then adding nano-silicon oxide and nano-aluminum oxide, heating and ultrasonically reacting, then centrifugally washing, and drying at room temperature to obtain the modified nanoparticles; S2, blending the modified nanoparticles with other ingredients, feeding them into a twin-screw extruder for melt blending, and extruding them to obtain the acid- and alkali-resistant plastic.

2. The acid and alkali corrosion resistant plastic according to claim 1, characterized in that: The molecular weight of the polypropylene is 8-15w.

3. The acid and alkali corrosion resistant plastic according to claim 1, characterized in that: The nucleating agent is selected from di(p-methylbenzylidene)sorbitol.

4. The acid and alkali corrosion resistant plastic according to claim 1, characterized in that: The antioxidant is selected from antioxidant 1076, antioxidant 1024 or antioxidant 1010.

5. The acid and alkali corrosion resistant plastic according to claim 1, characterized in that: The heating temperature is 90°C-100°C.

6. The acid and alkali corrosion resistant plastic according to claim 1, characterized in that: The melting temperature is 180°C-200°C.

Citation Information

Patent Citations

  • Polyurethane and polypropylene nano modified material

    CN102838866A

  • Polypropylene composition for plastic inner container of water heater and preparation method thereof

    CN103073798B

  • Degradable wood-bamboo-plastic composite foam packaging material and preparation method thereof

    CN109575543A

  • Anti-aging high-transparency high-strength polypropylene plastic barrel and preparation method thereof

    CN109705473A